2021
DOI: 10.3389/fneur.2021.675917
|View full text |Cite
|
Sign up to set email alerts
|

Pipeline Embolization Device for the Treatment of Ruptured Intracerebral Aneurysms: A Multicenter Retrospective Study

Abstract: Background and Purpose: The utilization of flow diversion for ruptured intracerebral aneurysms (IAs) is still limited. We aimed to demonstrate our multicenter experience using the pipeline embolization device (PED) for ruptured IAs that were difficult to treat by clipping and coiling.Methods: Thirty-eight patients with ruptured IAs who underwent PED treatment from 2015 to 2020 were retrospectively reviewed. Factors associated with procedure-related stroke (ischemic and hemorrhagic) and clinical and angiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Endovascular SAC therapy is typically more frequently used than FD in wide-neck ruptured cerebral aneurysms due to the increased risk of periprocedural bleeding and ischemic complications from using FD in ruptured aneurysms, especially in the acute phase. 33 However, Bechan et al showed the rate of short-term complications from SAC in ruptured aneurysms was ten times higher than in unruptured aneurysms. 11 A higher complication rate was related to ruptured aneurysm treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Endovascular SAC therapy is typically more frequently used than FD in wide-neck ruptured cerebral aneurysms due to the increased risk of periprocedural bleeding and ischemic complications from using FD in ruptured aneurysms, especially in the acute phase. 33 However, Bechan et al showed the rate of short-term complications from SAC in ruptured aneurysms was ten times higher than in unruptured aneurysms. 11 A higher complication rate was related to ruptured aneurysm treatment.…”
Section: Discussionmentioning
confidence: 98%
“…An analysis of outcomes for the other main treatment options for complex intracranial aneurysms highlights the significant challenges of managing this patient population. Flow diversion is the main endovascular option for the treatment of nonsaccular ruptured aneurysms, but is associated with a 21 to 26% rate of ischemic/hemorrhagic complications with use of either standard devices and dual anti-platelet regimens, or newer devices and single agent anti-platelets across all anatomic sites (4,5). While good neurologic outcomes have been reported with flow diversion for the treatment of fusiform VA aneurysms involving the PICA origin (representing 50% of the cases in the series), complete aneurysm occlusion occurs in <60% of cases, while PICA/VA occlusion can occur in up to 10% of cases (47).…”
Section: Discussionmentioning
confidence: 99%
“…Intrasaccular devices similarly have the potential to change treatment paradigms for selected widenecked saccular aneurysms (2). Limitations to these technologies nonetheless exist, particularly in the setting of ruptured aneurysms where flow diversion (or stent/coil constructs) requires the use of dual anti-platelet agents (increasing the risk of hemorrhage with ventricular catheters), and both flow diversion and intrasaccular devices can often have continued aneurysm filling (maintaining a small but significant risk of re-rupture) (3,4). Although newer flow diversion technologies are being investigated that require only a single anti-platelet agent, concerns regarding significant morbidity and mortality from ischemic complications or post-treatment aneurysmal re-bleeding (occurring in up to 21% of patients) remain based on data from preliminary studies (5).…”
Section: Introductionmentioning
confidence: 99%
“…10 Moreover, the stasis and the 3D scaffold-like coil design enable thrombus formation within the aneurysm to interfere with blood flow to the aneurysm wall, specifically the rupture site. 11 A study conducted by applying computational dynamics demonstrated that an FD combined with coiling considerably reduced the intraaneurysmal flow velocity and shear stress on the aneurysm wall compared to an FD alone, and further lowered the risk of aneurysm rupture and accelerated thrombosis. 12 Recent retrospective studies have also validated the benefit of this treatment strategy in lowering the risk of perioperative rebleeding.…”
Section: Discussionmentioning
confidence: 99%